Use of Recombination-Mediated Genetic Engineering for Construction of Rescue Human Cytomegalovirus Bacterial Artificial Chromosome Clones. (1st March 2012) - Dulal, Kalpana; Silver, Benjamin; Zhu, Hua
Abstract : Bacterial artificial chromosome (BAC) technology has contributed immensely to manipulation of larger genomes in many organisms including large DNA viruses like human cytomegalovirus (HCMV). The HCMV BAC clone propagated and maintained inside E. coli allows for accurate recombinant virus generation. Using this system, we have generated a panel of HCMV deletion mutants and their rescue clones. In this paper, we describe the construction of HCMV BAC mutants using a homologous recombination system. A gene capture method, or gap repair cloning, to seize large fragments of DNA from the virus BAC in order to generate rescue viruses, is described in detail. Construction of rescue clones using gap repair cloning is highly efficient and provides a novel use of the homologous recombination-based method in E. coli for molecular cloning, known colloquially as recombineering, when rescuing large BAC deletions. This method of excising large fragments of DNA provides important prospects for in vitro homologous recombination for genetic cloning.